2012
DOI: 10.1089/neu.2012.2385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Combined Treatment Paradigm Consisting of Environmental Enrichment and the 5-HT1A Receptor Agonist Buspirone after Experimental Traumatic Brain Injury

Abstract: Environmental enrichment (EE) and serotonin 1A (5-HT 1A )-receptor agonists provide significant benefit after experimental traumatic brain injury (TBI). The aim of this study was to test the hypothesis that combining these therapies would produce an effect that is more robust than either therapy alone. Anesthetized adult male rats received a cortical impact or sham injury and then were randomly assigned to EE or standard (STD) housing where they received either buspirone (0.3 mg/kg) or vehicle (1.0 mL/kg) once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 56 publications
5
63
1
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]36 EE alone, however, did not lead to an increase in memory retention, which is in contrast to that seen in adult models. 23,26,29,33 As reported for Experiment 1, the buspirone (0.1 mg/kg) STD-housed group was also significantly better than the STD vehicle group in the MWM. The data also showed that the combination group (buspirone, 0.1 mg/ kg + EE) performed markedly better than the single therapy groups (i.e., EE plus vehicle and STD buspirone) in both the acquisition of spatial learning and memory retention, which suggests an additive effect.…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]36 EE alone, however, did not lead to an increase in memory retention, which is in contrast to that seen in adult models. 23,26,29,33 As reported for Experiment 1, the buspirone (0.1 mg/kg) STD-housed group was also significantly better than the STD vehicle group in the MWM. The data also showed that the combination group (buspirone, 0.1 mg/ kg + EE) performed markedly better than the single therapy groups (i.e., EE plus vehicle and STD buspirone) in both the acquisition of spatial learning and memory retention, which suggests an additive effect.…”
Section: Discussioncontrasting
confidence: 63%
“…[18][19][20][21][22][23][24][25][26] Likewise, EE has also been shown to confer neurobehavioral and histological benefits in adult male rats after CCI 20,23,[26][27][28][29][30][31][32][33][34] and fluid percussion brain injury. [35][36][37][38][39][40] Recently, the benefits of EE have also been extended to female rats after CCI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations